Density of the transition probability for one class of generalized diffusion processes - Osipchuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
The existence of the density of the transition probability is investigated for a generalized diffusion process with transport that satisfies a certain condition of integrability with respect to the Gaussian measure.